Information: the fuel for change - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The Panos Institute is an independent institute based in London, which works to promote sustainable development. Panos combines research with dissemination, providing information to those who need it in forms that can be readily understood and...